INVENTARISASI DAN IDENTIFIKASI BANGUNAN TUA POTENSIAL SEBAGAI OBYEK WISATA ARSITEKTURAL DI DESA JAMBLANG CIREBON - Aly, Sudianto; Suriansyah, Yasmin; Ritva Santoso, Amirani; Srikanti Wijayaputri, Caecilia; Subagio, Irma (Jurnal Riset Arsitektur, 2024)
Abstract - This article describes the results of Community Service activities (ABDIMAS) organized by the ABDIMAS Team, Architecture Study Program, Parahyangan Catholic University, Bandung, in collaboration with STTC, Cirebon College of Technology. The ABDIMAS topic is an inventory and identification of the architectural tourism potential of old buildings in Jamblang Village, Cirebon Regency, which aims to compile a heritage trail as an architectural tourist map of the old buildings of Jamblang Village Cirebon Regency. The results of the inventory and identification of buildings are eight old buildings that have the potential to be used as tourist attractions. This article further explains these eight buildings in an architectural description. There are four residential buildings in Chinese architectural style, one building in the form of a monastery, and three old buildings in Colonial style, one of which is the Chinese Lieutenant's House. Keywords: Architectural Tourism; Old Buildings; Heritage Trail